2023
DOI: 10.3389/fneur.2023.1216777
|View full text |Cite
|
Sign up to set email alerts
|

Burden and attributable risk factors of ischemic stroke in China from 1990 to 2019: an analysis from the Global Burden of Disease Study 2019

Abstract: BackgroundThe epidemiologic characteristics and attributable risk factors of ischemic stroke in China have changed over the past three decades. An up-to-date analysis on deaths, disability-adjusted life-years (DALYs), prevalence, incidence, and attributable risk factors of ischemic stroke for China is needed. This study aims to provide a comprehensive analysis of burden and attributable risk factors of ischemic stroke at national level in China by sex from 1990 to 2019.MethodsThis is a secondary analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Between 2013 and 2018, red meat consumption increased among Chinese adults, with the proportion consuming 100 g or more daily increasing by 10%, and male and female proportions of 49.7 and 34.9%, respectively ( 31 ). One study found that the IS disease burden attributed to a diet high in red meat in China is increasing, which may be related to changes in dietary habits among the Chinese population ( 7 ). As China undergoes economic development, dietary and lifestyle changes have increased the population’s exposure to risk factors for IS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2013 and 2018, red meat consumption increased among Chinese adults, with the proportion consuming 100 g or more daily increasing by 10%, and male and female proportions of 49.7 and 34.9%, respectively ( 31 ). One study found that the IS disease burden attributed to a diet high in red meat in China is increasing, which may be related to changes in dietary habits among the Chinese population ( 7 ). As China undergoes economic development, dietary and lifestyle changes have increased the population’s exposure to risk factors for IS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that a diet high in red meat is a critical risk factor for IS, leading to a consistent increase in deaths and disability-adjusted life years (DALYs) globally ( 6 ). China has the world’s highest number of IS deaths associated with high red meat intake ( 2 , 7 , 8 ). Nevertheless, the epidemiological features and evolving patterns of IS associated with high red meat consumption in China are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…A national platform for remote stroke centers was launched in 2014, and a network is currently being developed to guide timely stroke treatment in rural hospitals 34 . It is encouraging that a low-fiber diet has been declining in recent years 11 , 35 . Compared to GBD 2017, GBD 2019 showed a significant improvement in the proportion of dietary fiber leading to a poor stroke prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another related study conducted a descriptive analysis of the 30-year trends in incident cases, prevalence, mortality, and DALYs due to IS in China. It also ranked the severity of relevant risk factors in different years [14]. Additionally, clinical trial studies prioritized predictive risk factors for IS in Chinese subjects, revealing that high blood pressure and LDL-C concentration (≤40 mg/dL) are significant predictors of IS risk [15].…”
Section: Introductionmentioning
confidence: 99%